Influence of water-to-cement ratio on the compressive strength of cement-biochar-spent ion exchange resins matrix - Zalina Laili,; Muhamad Samudi Yasir,; Mohd Abdul Wahab Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The influence of water-to-cement ratio (w/c) on the compressive strength of cement-biochar-spent resins matrix was investigated. Spent resins waste from nuclear reactor operation was solidified using cement with w/c ranging from 0.35 to 0.90 by weight. In this study, biochar was used as a cement admixture. Some properties of spent resins and biochar were determined prior to the formulation study. Compressive strength of harden cement-biochar-spent resins matrix was determined at 28 days. The compressive strength of cement-biochar-spent resins matrix was found to depend on the w/c and the amount of spent resins added to the formulation. The immersion test of cement-biochar-spent resins matrix showed no significant effects of cracking and swelling. The compressive strength of the cement-biochar-spent resins matrix increased after two weeks in water immersion test.